Plastid and cytoplasmic origins of 1O2-mediated transcriptomic responses - Koh, Eugene; Brandis, Alexander; Fluhr, Robert (Frontiers in Plant Science, 2022)
The reactive oxygen species singlet oxygen, 1O2, has an extremely short half-life, yet is intimately involved with stress signalling in the cell. We previously showed that the effects of 1O2 on the transcriptome are highly correlated with 80S ribosomal arrest due to oxidation of guanosine residues in mRNA. Here, we show that dysregulation of chlorophyll biosynthesis in the flu mutant or through feeding by δ-aminolevulinic acid can lead to accumulation of photoactive chlorophyll intermediates in the cytoplasm, which generates 1O2 upon exposure to light and causes the oxidation of RNA, eliciting 1O2-responsive genes. In contrast, transcriptomes derived from DCMU treatment, or the Ch1 mutant under moderate light conditions display commonalties with each other but do not induce 1O2 gene signatures. Comparing 1O2 related transcriptomes to an index transcriptome induced by cycloheximide inhibition enables distinction between 1O2 of cytosolic or of plastid origin. These comparisons provide biological insight to cases of mutants or environmental conditions that produce 1O2.